2011
DOI: 10.1111/j.1464-410x.2010.10038.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic adrenalectomy in urological centres – the experience of the German Laparoscopic Working Group

Abstract: Study Type – Practice patterns (retrospective cohort) Level of Evidence 2b OBJECTIVE • To evaluate the safety and feasibility of laparoscopic adrenalectomy (LA) performed in several German centres with different laparoscopic experience, as LA has become the gold‐standard approach for benign surgical adrenal disorders; however, for solitary metastasis or primary adrenal cancer its precise role is uncertain. PATIENTS AND METHODS • The data of 363 patients who underwent a LA were prospectively collected in 23 cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 25 publications
1
26
0
2
Order By: Relevance
“…In a multicenter study, Greco et al demonstrated that laparoscopic surgery for malignant adrenal tumors should be performed only in high-volume centers with at least ≥10 adrenalectomies per year [26]. We did not specifically analyze and compare oncologic outcomes from the studies included in the present meta-analysis because only two of them partially reported on these outcomes.…”
Section: Critical Analysismentioning
confidence: 99%
“…In a multicenter study, Greco et al demonstrated that laparoscopic surgery for malignant adrenal tumors should be performed only in high-volume centers with at least ≥10 adrenalectomies per year [26]. We did not specifically analyze and compare oncologic outcomes from the studies included in the present meta-analysis because only two of them partially reported on these outcomes.…”
Section: Critical Analysismentioning
confidence: 99%
“…12,13 Laparoscopic adrenalectomy (LA) was initially described in 1992 and has become the gold standard for treatment of benign adrenal tumors. [14][15][16][17] In multiple retrospective studies, LA is associated with lower operative complication rates, shorter hospital stays, reduced 30-day morbidity, and lower overall costs. [18][19][20][21][22] However, the role of LA for treatment of patients with ACC remains controversial, particularly as it relates to its oncologic outcomes.…”
mentioning
confidence: 99%
“…If there is no evidence of metastasis, size alone does not predict malignancy in pheochromocytomas [21]. Greco et al [22] conducted a multicenter study and reported that the upper limit for adrenalectomy could be as high as 10-14 cm for very experienced surgeons. In our series, a pheochromocytoma measuring 9 cm in diameter was removed successfully using the retroperitoneal approach with a blood loss of 50 ml.…”
Section: Discussionmentioning
confidence: 99%